(untitled) (American Journal of Multidisciplinary Research and Innovation, 2023)
To adapt to the current pandemic, the higher education system in hospitality management must shift away from traditional classroom to online classroom settings. Successful hospitality management education requires internship experiences as it eases the students’ transition between education and employment. However, delivering it through virtual channels presents special challenges. Thus, this research aimed to assess how hospitality management students view the virtual internship (VI) and work-integrated learning (WIL) outcomes during pandemic. This study employed descriptive method to identify the different variables of the study and presents quantitative research that utilized online survey method to gather data. The respondents of the study were the fourth year Bachelor of Science in Hospitality Management (BSHM) students (n=35) from the College of Business and Management of the Mindoro State University-Calapan City Campus who undertaken the virtual internship for the second semester of AY 2021-2022. Results of the study showed that VI was the best alternative to face-to-face internship as the students felt secured and less exposed on the threats of COVID-19, however, the VI felt short of the means for them to ask questions and clarify difficulties as well as failing to form networking opportunities. Students also believed it enhanced their skills and have advanced in their practical knowledge but somehow, they lack in creating opportunity to work in a genuine hospitality industry setting. It is recommended to conduct a hybrid internship, both virtual and on-site, to create a chance for the hospitality management students to have an authentic workplace setting.